DNA-Methylation and Body Composition in Preschool Children: Epigenome-Wide-Analysis in the European Childhood Obesity Project (CHOP)-Study. Issue 1 (December 2017) - Rzehak, Peter; Covic, Marcela; Saffery, Richard; Reischl, Eva; Wahl, Simone; Grote, Veit; Weber, Martina; Xhonneux, Annick; Langhendries, Jean-Paul; Ferre, Natalia; Closa-Monasterolo, Ricardo; Escribano, Joaquin; et al.
Abstract Adiposity and obesity result from the interaction of genetic variation and environmental factors from very early in life, possibly mediated by epigenetic processes. Few Epigenome-Wide-Association-Studies have identified DNA-methylation (DNAm) signatures associated with BMI and body composition in children. Body composition by Bio-Impedance-Analysis and genome-wide DNAm in whole blood were assessed in 374 pre-school children from four European countries. Associations were tested by linear regression adjusted for sex, age, centre, education, 6 WBC-proportions according to Houseman and 30 principal components derived from control probes. Specific DNAm variants were identified to be associated with BMI (212), fat-mass (230), fat-free-mass (120), fat-mass-index (24) and fat-free-mass-index (15). Probes in genesSNED1 (IRE-BP1 ), KLHL6, WDR51A (POC1A ), CYTH4-ELFN2, CFLAR, PRDM14, SOS1, ZNF643 (ZFP69B ), ST6GAL1, C3orf7 0, CILP2, MLLT4 and ncRNALOC101929268 remained significantly associated after Bonferroni-correction ofP -values. We provide novel evidence linking DNAm with (i) altered lipid and glucose metabolism, (ii) diabetes and (iii) body size and composition in children. Both common and specific epigenetic signatures among measures were also revealed. The causal direction with phenotypic measures and stability of DNAm variants throughout the life course remains unclear and longitudinal analysis in other populations is required. These findings give support for potential epigenetic programming of body composition and obesity.